2009
DOI: 10.1111/j.1529-8027.2009.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of small‐fiber neuropathy

Abstract: The aim of this study was to evaluate the etiology in a group of 84 patients with painful sensory neuropathy with predominant small-fiber dysfunction (54 men and 30 women, median: 58; range: 25-83 years) recruited from a population of the South Moravian region of the Czech Republic. Involvement of small nerve fibers was verified by abnormal thermal thresholds and/or reduced intraepidermal nerve fiber densities. Motor signs or symptoms or significant clinical signs of sensory large-fiber involvement were exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 26 publications
3
56
1
3
Order By: Relevance
“…5,6,9 In this study we show, in 8 of 28 (28.6%) patients with skin biopsyand QST-confirmed I-SFN, missense mutations in the SCN9A gene, which encodes a voltage-gated sodium channel, Na V 1.7, that is present within small peripheral nerve fibers. Electrophysiological analysis demonstrated gain of function changes in the mutant channels and showed that the mutations share the common feature of rendering DRG neurons hyperexcitable.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…5,6,9 In this study we show, in 8 of 28 (28.6%) patients with skin biopsyand QST-confirmed I-SFN, missense mutations in the SCN9A gene, which encodes a voltage-gated sodium channel, Na V 1.7, that is present within small peripheral nerve fibers. Electrophysiological analysis demonstrated gain of function changes in the mutant channels and showed that the mutations share the common feature of rendering DRG neurons hyperexcitable.…”
Section: Discussionmentioning
confidence: 93%
“…5,6,9 Observations of autosomal dominant inheritance suggest a genetic origin for the small fiber involvement that is seen in burning feet syndrome. 10 However, no specific gene has been linked to, or mutations identified in, patients with adult onset I-SFN.…”
mentioning
confidence: 98%
“…Diabetes and toxic causes are best known [80], but several systemic autoimmune conditions are also associated [14]. In addition to ganglionitis, Sjögren's also causes painful distal SFPN [81].…”
Section: Small-fiber Polyneuropathymentioning
confidence: 99%
“…SFN is associated with diabetes, HIV infection, and chemotherapy treatment, but many patients suffer from idiopathic SFN (3)(4)(5). SFN patients can exhibit a large variety of symptoms, including loss of sensation and chronic pain.…”
mentioning
confidence: 99%